Jet-Grouting Technology for Reinforcement Strata Disturbance After Sand Mining - Fu, Tao; Wang, Kai; Ren, Xiaoqian; Zhu, Zhixin; Wang, Liang (Frontiers in Built Environment, 2022)
During the construction of a bridge, due to the deep sand mining in the riverbed at the bridge site, a sand mining disturbance stratum is formed at the bridge site, and it has an impact on the construction quality of the pile group foundation. In this paper, in view of the special geological conditions caused by sand mining, the high-pressure jet grouting method was used to reinforce the disturbed stratum at the bridge site, and a scheme and key construction technology high-pressure rotary jet pile grouting to reinforce the disturbed stratum caused by sand mining is proposed. A three-dimensional finite element model of the pile group before and after reinforcement of the disturbed stratum by high-pressure jet grouting method is established. The distribution characteristics of the lateral displacement of the borehole wall in the disturbed stratum before and after reinforcement are compared and analysed. Application on an actual bridge proves that the high-pressure jet grouting method has a good reinforcement effect on the disturbed stratum, which effectively solves the phenomenon of hole expansion and pile casing falling in the construction process of the pile foundation caused by sand mining disturbance and improves the working performance and construction quality of the pile group foundation. The high-pressure jet grouting technique for reinforcement of disturbed stratum is proved to be effective in practice.